The curious case of the disappearing piRNAs. - Sarkies, P. (Wiley interdisciplinary reviews. RNA, 2024)
Small non-coding RNAs are key regulators of gene expression across eukaryotes. Piwi-interacting small RNAs (piRNAs) are a specific type of small non-coding RNAs, conserved across animals, which are best known as regulators of genome stability through their ability to target transposable elements for silencing. Despite the near ubiquitous presence of piRNAs in animal lineages, there are some examples where the piRNA pathway has been lost completely, most dramatically in nematodes where loss has occurred in at least four independent lineages. In this perspective I will provide an evaluation of the presence of piRNAs across animals, explaining how it is known that piRNAs are missing from certain organisms. I will then consider possible explanations for why the piRNA pathway might have been lost and evaluate the evidence in favor of each possible mechanism. While it is still impossible to provide definitive answers, these theories will prompt further investigations into why such a highly conserved pathway can nevertheless become dispensable in certain lineages. This article is categorized under: Regulatory RNAs/RNAi/Riboswitches > Biogenesis of Effector Small RNAs RNA Evolution and Genomics > RNA and Ribonucleoprotein Evolution.